Case Report: Complex Treatment Using Vibroacoustic Therapy in a Patient With Co-Infection and COVID-19 - Bekniyazova, Assema Zh.; Kadralinova, Assiya; Konkayeva, Maiya E.; Yeltayeva, Aigerim A.; Konkayev, Aidos K. (Frontiers in Medicine, 2022)
The present report highlights a case of a successful treatment of a 59-year-old patient experienced pain, swelling, hyperemia, the presence of a wound of the right knee joint, impaired function of the right lower limb, weakness, fatigue, and labored breathing. Sepsis was detected in the patient as a result of a periprosthetic infection with concomitant severe COVID-19. The patient was admitted to the hospital for 59 days, with 57 days of treatment of the patient at the intensive care unit. A therapy of multiple organ failure involved complex treatment using antiviral and combined antibiotic therapy, taking into account the sensitivity of the pathogen to antibiotics; glucooticoid therapy; anticoagulant therapy; the concept of noninvasive ventilation; and vibroacoustic pulmonary therapy as a method of physiotherapy as well. An integrated approach using a vibroacoustic device in the therapy of the pa-tient with sepsis due to periprosthetic infection with concominant coronavirus infection had had a positive effect despite the lack of etiological treatment against the COVID-19.